Answer:
[tex] \displaystyle 6({3}^{n} - 1)- 4( {2}^{n} - 1 ) [/tex]
Step-by-step explanation:
we would like to evaluate the following sum of geometric series:
[tex] \displaystyle \sum_{k = 1}^n (4 \cdot {3}^{k} - {2}^{k + 1}) [/tex]
to do so recall the Substracting property of partial sum Thus,
[tex] \displaystyle \sum_{k = 1}^n (4 \cdot {3}^{k} )- \sum_{k = 1}^n({2}^{k + 1}) [/tex]
rewrite $2^{k+1}$ as 2•2^k:
[tex] \displaystyle \sum_{k = 1}^n (4 \cdot {3}^{k} )- \sum_{k = 1}^n({2}^{k } \cdot 2) [/tex]
utilize constant property of partial sum:
[tex] \displaystyle 4\sum_{k = 1}^n ({3}^{k} )- 2\sum_{k = 1}^n({2}^{k } ) [/tex]
factor out 2:
[tex] \displaystyle 2 \left(2\sum_{k = 1}^n ({3}^{k} )- \sum_{k = 1}^n({2}^{k } ) \right)[/tex]
calculate the sum:
[tex] \displaystyle 2 \left( \frac{ 6({3}^{n} - 1)}{2} - 2( {2}^{n} - 1 ) \right)[/tex]
distribute:
[tex] \displaystyle \boxed{6({3}^{n} - 1)- 4( {2}^{n} - 1 ) }[/tex]
and we're done: